IMPLEMENTATION OF THE CORPORATE SOCIAL RESPONSIBILITY PROGRAM: SHOPEE FOR THE BAMBOO COMMUNITY OF PRINGGODANI - DESSY ISFIANADEWI; TEZZA ADRIANSYAH ANWAR (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
This study aims to determine the extent of the benefits of implementing CSR programs provided by companies to the public. Specifically, this research was carried out on the implementation of CSR programs carried out by Shopee, Shopee for the Country, for the community, in this case, the Pringgodani community as the recipient of assistance. This village is widely known for bamboo crafts made by craftsmen in the village. This study use three methods of data collection, namely: interview method, observation, and documentation to maintain data validity and reliability. The results of this study note that CSR programs carried out by Shopee, Shopee for the Country to the Pringgodani Community include: UMKM (Community) education and training assistance in workshop building, capital assistance in the form of purchasing production machinery, assistance with product promotion and marketing partners online. The success of the Shopee CSR program to improve and develop the Community's potential has provided positive results and impacts even though it has not been fully optimized. This is because there are still some obstacles in addition to the existence of several supporting factors. It can be concluded that the current needs of the Community are the existence of education and ongoing assistance to craftsmen in producing quality products and running businesses that are ready to compete. Suggestions, CSR programs should be delivered directly to the recipient community without intermediaries, so that the program implementation can be carried out directly by the community.